Optical excitation In2O3 / PPy / g-C3N4 heterojunction material room temperature CO2 gas sensing material and preparation method thereof
Through the sandwich structure of In2O3/PPy/g-C3N4 heterojunction material, in-situ chemical polymerization and visible light excitation technology, efficient detection of CO2 gas at room temperature is achieved, and the inadequate detection capability of CO2 sensors at room temperature in the prior art is solved. The problem of this paper significantly improves detection sensitivity and response speed.
Patent Information
- Application Number
- CN202411584021.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Most of the existing CO2 sensors need to operate under high temperature conditions, have high energy consumption and have an impact on the environment, and cannot efficiently and sensitively detect CO2 gas at room temperature.
Using In2O3/PPy/g-C3N4 heterojunction material, PPy is grown on the In2O3 surface by in-situ chemical polymerization and combined with g-C3N4 nanosheets to form a sandwich structure, and the detection of low-concentration CO2 gas at room temperature is achieved using visible light excitation.
It significantly improves the sensitivity and response speed of the material, can accurately detect CO2 concentrations as low as ppm level at room temperature, has higher gas sensitivity and stability, is better than a single In2O3 material, and is suitable for rapid detection of CO2.
Smart Images

Figure CN119264422A_ABST
Abstract
Description
1. Technical Field
[0001] The present invention relates to the field of environmental monitoring and sensing technology, and specifically to a sensing material for detecting CO2 gas using a light-excited In2O3 / PPy / g-C3N4 heterojunction material at room temperature and a preparation method thereof. 2. Background Technology
[0002] With the acceleration of the global industrialization process, the large-scale burning of fossil fuels such as coal and oil has led to an increase in the concentration of CO2 in the atmosphere year by year, which not only exacerbates the greenhouse effect, but also poses a serious threat to the ecosystem and human health. Therefore, it is particularly important to develop an efficient, accurate and environmentally friendly CO2 sensor. Most of the currently available CO2 sensors need to work under high temperature conditions, with high energy consumption and impact on the environment. Therefore, the development of a sensing material that can efficiently and sensitively detect CO2 at room temperature is of great significance for environmental protection and energy conservation.
[0003] Polypyrrole (PPy) is a conductive polymer material with the advantages of high conductivity, controllable synthesis and good biocompatibility. It is widely used in various fields, including sensors, batteries, solar cells, optoelectronics and biomedical engineering. PPy can play a very important role in semiconductor heterojunction materials because PPy has high electrical conductivity and can effectively improve the charge transfer performance of semiconductor materials. When PPy is added to semiconductor materials, it can form a continuous conduction channel, making it easier for electrons to migrate in the material. The nitrogen atoms and pyrrole rings can provide additional chemical adsorption sites, which help to enhance the interaction between the material and CO2 gas. Due to its good electrical conductivity and the provision of chemical adsorption sites, PPy can improve the sensitivity of semiconductor materials to CO2. At the same time, it can improve the selectivity of materials to CO2 and reduce the interference of other gases. Therefore, the introduction of polypyrrole can significantly improve the gas-sensitive properties of semiconductor heterojunction materials to CO2. In addition, PPy has excellent visible light absorption ability. The composite with In2O3 / PPy will significantly enhance the visible light absorption ability, broaden the visible light response range, and improve the CO2 gas response under visible light irradiation.
[0004] Due to the high conductivity and abundant chemical adsorption sites of PPy, it means that it can generate detection signals at lower CO2 concentrations, thereby increasing the scope and accuracy of its application. Since PPy enhances the charge transfer efficiency and the chemical adsorption capacity of the material, In2O3 / PPy / g-C3N4 can respond faster to CO2, which is very important for applications that require rapid and accurate detection of CO2. In2O3 / PPy / g-C3N4 with the addition of PPy has enhanced gas-sensing performance and stability due to its improved material structure. Therefore, from the three aspects of sensitivity, response speed and stability, the gas-sensing performance of In2O3 / PPy / g-C3N4 to CO2 is better than that of In2O3 / g-C3N4.
[0005] Based on the above considerations, the present invention adopts in-situ chemical polymerization to successfully grow PPy on the surface of In2O3, and in-situ polymerizes g-C3N4 to obtain a sandwich structured In2O3 / PPy / g-C3N4 ternary heterojunction gas-sensitive material. III. Summary of the invention
[0006] The present invention aims to provide a sensing material for detecting CO2 gas at room temperature using a light-excited In2O3 / PPy / g-C3N4 heterojunction material and a preparation method thereof. The sensing material is a one-dimensional tubular structured In2O3 / PPy / g-C3N4 composite heterojunction material, which utilizes a heterojunction to increase the number of surface carriers of the gas-sensitive material and improve the disadvantage that photogenerated electron-hole pairs of a single semiconductor material are easy to recombine, and uses a visible light-excited semiconductor heterojunction material to achieve low-concentration CO2 gas sensing at room temperature.
[0007] In order to achieve the technical purpose of the present invention, the technical solution adopted by the present invention is as follows:
[0008] 1. Preparation of In2O3 hollow tubes: First, the In-MIL-68 precursor was synthesized by a hydrothermal method, and then calcined in an air atmosphere to obtain an In2O3 hollow tubular structure.
[0009] 2. Preparation of g-C3N4 nanosheets: g-C3N4 nanosheets were prepared by simply heating urea, and pure g-C3N4 nanosheets were obtained by centrifugation and washing.
[0010] 3. Preparation of PPy: Pyrrole was added dropwise to FeCl3·6H2O solution, ultrasonically reacted for 12 h, rinsed alternately with anhydrous ethanol and ultrapure water, and placed in a vacuum drying oven for 12 h to obtain black PPy powder.
[0011] 4. Preparation of In2O3 / PPy: Pyrrole was added to the FeCl3·6H2O solution, and then added dropwise to the suspension of In2O3 and pyrrole, and the mixture was stirred and polymerized for 10 hours. The product was centrifuged, rinsed alternately with anhydrous ethanol and ultrapure water, and placed in a vacuum drying oven for 12 hours to obtain gray-black In2O3 / PPy powder.
[0012] 5. Preparation of g-C3N4 / PPy: Pyrrole was added to the suspension of g-C3N4 nanosheets and ultrasonically treated for 30 min. FeCl3·6H2O was added dropwise to the suspension of g-C3N4 and pyrrole for polymerization for 10 h. The mixture was rinsed and filtered alternately with anhydrous ethanol and ultrapure water. The precipitate was placed in a vacuum drying oven for 12 h to obtain black g-C3N4 / PPy powder.
[0013] 6. Preparation of In2O3 / PPy / g-C3N4 heterojunction material: In2O3 / g-C3N4 heterojunction material was prepared by in-situ growth method and subsequent calcination treatment, wherein the photoresponse performance of the material was optimized by adjusting the addition ratio of g-C3N4. In2O3 and g-C3N4 were ultrasonically treated, pyrrole was added to the suspension and ultrasonic dispersion was continued, and then FeCl3·6H2O was added to the suspension of In2O3, pyrrole and g-C3N4, and the reaction was continued by stirring for 10 hours. The product was centrifuged, rinsed and filtered alternately with anhydrous ethanol and ultrapure water, and placed in a vacuum drying oven for 12 hours to obtain black In2O3 / PPy / g-C3N4 powder. The obtained In2O3 / PPy / g-C3N4 powder was placed in a tube furnace and heated to 350°C to obtain a gray-black In2O3 / PPy / g-C3N4 heterojunction powder material.
[0014] 7. Characterization and analysis: SEM and TEM were used to observe the morphology and confirm the microstructure of the material. XRD and FT-IR were used to determine the crystal structure and chemical composition of the material. UV-Vis and PL tests were used to evaluate the optical properties and electron-hole separation efficiency of the material.
[0015] 8. Sensing performance test: Different concentrations of CO2 were detected at room temperature and under visible light irradiation. The results showed that the In2O3 / PPy / g-C3N4 heterojunction material has extremely high sensitivity to CO2 and a detection limit as low as ppm, which is significantly better than a single In2O3 material.
[0016] Preferably, in step 1, 468 mg of In(NO3)3·xH2O and 180 mg of H2BDC are weighed and added into 40 ml of DMF.
[0017] Preferably, in step 2, 10 g of urea is weighed and placed in a tubular furnace, the heating rate is set to 2° C. / min, and heated to 550° C. and maintained for 4 h.
[0018] Preferably, in step 3, 2.96 g of FeCl3·6H2O is weighed and dissolved in 20 ml of ultrapure water, and 0.5 ml of pyrrole is gradually added to 30 ml of ultrapure water, and ultrasonic treatment is performed for 30 min.
[0019] Preferably, in step 3, FeCl3·6H2O aqueous solution is gradually added dropwise to the pyrrole dispersion in a 3°C water bath and the reaction is continued for 12 hours.
[0020] Preferably, in step 4, 100 mg of In2O3 hollow tube is weighed and placed in 35 ml ultrapure water, 40 μl of pyrrole is added thereto, and ultrasonic treatment is performed for 30 min. FeCl3·6H2O aqueous solution is added dropwise to the suspension of In2O3 and pyrrole, and the polymerization is stirred for 10 h.
[0021] Preferably, in step 5, 100 mg of g-C3N4 nanosheets are weighed and placed in 35 ml of ultrapure water, 40 μl of pyrrole is added thereto, and ultrasonic treatment is performed for 30 min. FeCl3·6H2O aqueous solution is added dropwise to the suspension of g-C3N4 and pyrrole at 40°C for polymerization for 10 h.
[0022] Preferably, in step 6, 100 mg of In2O3 and 50 mg of g-C3N4 are weighed and added to ultrapure water for ultrasonic dispersion; 20 μl, 40 μl, and 60 μl of pyrrole are respectively added dropwise to a beaker for ultrasonic dispersion for 30 minutes.
[0023] Preferably, in step 6, an aqueous solution of FeCl3·6H2O is added dropwise to the suspension of In2O3, pyrrole and g-C3N4, and the reaction is continued by stirring for 10 h.
[0024] Preferably, in step 6, the In2O3 / PPy / g-C3N4 powder is placed in a tube furnace and heated to 350°C for short-time (30 min) annealing.
[0025] Preferably, in step 8, an electrochemical workstation It is used for testing to obtain a curve of current variation with time, and data conversion is performed to obtain information of resistance variation with time, thereby obtaining information of CO2 concentration variation.
[0026] Figure 1These are SEM and TEM images of In2O3 / PPy / g-C3N4 heterojunction materials. PPy nanoparticles are evenly dispersed and loaded on the surface of g-C3N4 nanosheets. This proves that PPy nanoparticles are successfully polymerized in situ on g-C3N4. The hollow structure of the material can be seen in the TEM image of the composite material, but the tube wall is not obvious. The in situ polymerization of PPy and g-C3N4 has an effect on the hollow tubular structure of In2O3. From the HRTEM image, it can be observed that the In2O3 (222) crystal plane corresponding to the interplanar spacing of 0.291nm, and at the same time, it is observed that the In2O3 outer layer is wrapped with PPy, and the sandwich structure of g-C3N4 is wrapped in the outer layer of PPy.
[0027] Figure 2 This is the XRD diagram of In2O3 / PPy / g-C3N4 heterojunction material. It is found that the addition of g-C3N4 has an impact on the crystallization properties of PPy. Due to the large specific surface area of g-C3N4 and other reasons, there may be a certain interface interaction between PPy and g-C3N4, which hinders the regular arrangement of PPy polymer chains and leads to changes in crystallinity.
[0028] Figure 3 This is the FT-IR image of In2O3 / PPy / g-C3N4 heterojunction material. The PPy is located at 1548cm -1 The characteristic peak at 1017 cm is the C=C vibration peak of the pyrrole ring. -1 The corresponding stretching vibrations of CN are at 1239, 1316, 1406, and 1637 cm in g-C3N4. -1 The characteristic peaks at are consistent with the stretching vibration peaks of aromatic CN and C=N heterocycles, proving the successful synthesis of PPy and g-C3N4.
[0029] Figure 4 This is the XPS spectrum of In2O3 / PPy / g-C3N4 heterojunction material. After compounding with PPy, the characteristic peaks of In2O3 / PPy / g-C3N4 move toward the direction of higher binding energy, including lattice oxygen (530.3eV), vacancy oxygen (531.9eV) and adsorbed oxygen (533.2eV). This proves that there is a strong electron transfer effect between PPy and g-C3N4 and In2O3.
[0030] Figure 5UV-vis DRS tests were performed on PPy, g-C3N4, g-C3N4 / PPy, In2O3 / g-C3N4 and In2O3 / PPy / g-C3N4 to analyze the visible light absorption range, separation efficiency of photogenerated carriers, and semiconductor band gap information. The absorption band edge of the In2O3 / PPy / g-C3N4 heterojunction material red-shifted, and compared with In2O3 / g-C3N4, it has significantly enhanced visible light absorption capacity, extending to the entire visible light absorption range. This is due to PPy's high carrier transport ability, strong visible light absorption ability, and the formation of heterojunctions.
[0031] Figure 6 In2O3, PPy, g-C3N4 and In2O3 / PPy / g-C3N4 heterojunction materials were tested under visible light irradiation and dark conditions. The heterojunction material significantly improved the situation that the single material could not fully recover without visible light irradiation. It was proved that the heterojunction and visible light irradiation can improve the responsiveness and recovery ability. Among them, PPy showed a p-type response, that is, the resistance decreased after contacting the oxidizing gas.
[0032] Figure 7 To further prove that In2O3 / PPy / g-C3N4 mainly responds to CO2 in the air, the CO2 gas sensing performance of In2O3 / PPy / g-C3N4 was tested under visible light irradiation at room temperature. Different concentrations of CO2 and N2 were used alternately to obtain a dynamic response curve. As the CO2 gas concentration increases, the sensitivity also increases.
[0033] Figure 8 The effect of humidity on the sensing performance of gas-sensitive materials was evaluated by testing air with an increased concentration of 200 ppm of CO2 at different humidities. The pyrrolic nitrogen in PPy can provide additional adsorption sites for CO2, so In2O3 / PPy / g-C3N4 is less affected by humidity than In2O3 / g-C3N4.
[0034] Fig. 9 The gas-sensitive material is continuously and alternately exposed to air with a CO2 concentration of 120ppm to evaluate the sensing performance of the gas-sensitive material. After multiple continuous tests, the sensitivity curve of the heterojunction material did not show a significant shift, and In2O3 / PPy / g-C3N4 had a higher sensitivity.
[0035] The excellent effects of the present invention are as follows: 1. The In2O3 / PPy / g-C3N4 heterojunction material of the present invention shows a one-dimensional sandwich structure of uniformly loaded nanoparticles and nanosheets, PPy has a good adsorption effect on CO2, can generate higher photocurrent, can improve the sensitivity and response time of gas response, and is significantly better than a single semiconductor gas-sensitive material. The heterojunction material has great application potential in CO2 quantitative detection sensing.
[0036] 2. Utilize in-situ polymerization to polymerize PPy between In2O3 and g-C3N4. Further short-term calcination is performed to remove excess PPy on the surface to obtain a series of In2O3 / PPy / g-C3N4 heterojunction materials. Due to the loading of PPy, the carrier transmission mode between the In2O3 / g-C3N4 heterojunction is changed, and the visible light absorption capacity of the material is greatly improved. These changes can improve the charge separation efficiency of In2O3 / g-C3N4, increase the number of electrons on the surface of the material, and thus improve its sensing response to CO2.
[0037] 3. The In2O3 / PPy / g-C3N4 heterojunction material of the present invention realizes the sensing response to CO2 under visible light irradiation at room temperature. And it has a good fitting function relationship for CO2 of different concentrations and air with varying CO2 concentrations. It proves that the heterojunction material has great application potential in low-concentration CO2 detection, such as plant respiration detection, human respiration detection, CO2 gas leakage detection, etc. IV. Description of the drawings
[0038] Figure 1 SEM and TEM images of heterojunction materials;
[0039] Figure 2 is the XRD pattern of heterojunction material;
[0040] Figure 3 FT-IR image of heterojunction material;
[0041] Figure 4 This is the XPS spectrum of the heterojunction material;
[0042] Figure 5 UV-vis DRS and Tauc plot of heterojunction materials;
[0043] Figure 6 This is the sensing response curve of the heterojunction material to 50ppm CO2 gas;
[0044] Figure 7 The dynamic response curve of heterojunction material to different concentrations of CO2 under visible light irradiation;
[0045] Figure 8 The gas selectivity of heterojunction materials under visible light irradiation;
[0046] Fig. 9 Continuous multiple dynamic detection response curves and long-term stability tests for heterojunction materials; V. Specific implementation methods
[0047] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.
[0048] Example 1
[0049] A method for preparing a heterojunction sensing material for CO2 gas detection at room temperature, characterized by comprising the following steps:
[0050] (1) Preparation of In-MIL-68: Weigh 468 mg of In(NO3)3·xH2O and 180 mg of H2BDC respectively, add them into 40 ml of DMF and fully dissolve them, react in an autoclave at 120°C for 2 h, then centrifuge at 3500 r / min for 10 min, wash with anhydrous ethanol and ultrapure water alternately to filter out the white precipitate, and place it in a vacuum drying oven for 12 h to obtain a white powder sample, namely In-MIL-68.
[0051] (2) Preparation of In2O3 hollow tubes: The In-MIL-68 obtained above was placed in a tube furnace, heated to 120°C and maintained for 2 h, and then heated to 400°C and calcined for 2 h to obtain a white powder sample, which is the In2O3 hollow tube.
[0052] (3) Preparation of g-C3N4 nanosheets: 10 g of urea was weighed and placed in a tube furnace, heated to 550°C for 4 h to obtain light yellow g-C3N4. The g-C3N4 was stirred in ultrapure water for 4 h, ultrasonically dispersed for 1 h, and dried in a vacuum drying oven for 12 h to obtain light yellow g-C3N4 nanosheets.
[0053] (4) Preparation of PPy: Weigh 2.96 g of FeCl3·6H2O and add it to 20 ml of ultrapure water. Take 0.5 ml of pyrrole and gradually add it to 30 ml of ultrapure water, and treat it ultrasonically for 30 min. In a 3°C water bath, gradually add FeCl3·6H2O aqueous solution to the pyrrole dispersion and continue the reaction for 12 h. The obtained black product is placed in a vacuum drying oven at 40°C for 12 h to obtain black PPy powder.
[0054] (5) Preparation of In2O3 / PPy: Weigh 100 mg of In2O3 hollow tube and place it in 35 ml of ultrapure water, add 40 μl of pyrrole, and ultrasonicate for 30 min. Weigh 100 mg of FeCl3·6H2O and add it to 5 ml of ultrapure water, stir to fully dissolve, gradually add it dropwise to the suspension of In2O3 and pyrrole at 40°C, and stir to polymerize for 10 h. Centrifuge the product, rinse it alternately with anhydrous ethanol and ultrapure water, and place it in a vacuum drying oven at 40°C for 12 h to obtain gray-black In2O3 / PPy powder.
[0055] (6) Preparation of g-C3N4 / PPy: Weigh 100 mg of g-C3N4 nanosheets and place them in 35 ml of ultrapure water. Add 40 μl of pyrrole and ultrasonicate for 30 min. Weigh 100 mg of FeCl3·6H2O and add it to 5 ml of ultrapure water to fully dissolve. Gradually add it dropwise to the suspension of g-C3N4 and pyrrole at 40°C for polymerization for 10 h. Use anhydrous ethanol and ultrapure water to rinse and filter alternately. Place the precipitate in a vacuum drying oven at 40°C for 12 h to obtain black g-C3N4 / PPy powder.
[0056] (7) Preparation of In2O3 / PPy / g-C3N4 heterojunction material: Weigh 100 mg of In2O3 and 50 mg of g-C3N4 and add them to 35 ml of ultrapure water. Measure 40 μl of pyrrole and gradually drop it into the beaker and continue ultrasonic dispersion for 30 min. Weigh 100 mg of FeCl3·6H2O and add it to 5 ml of ultrapure water to fully dissolve. Gradually drop it into the suspension of In2O3, pyrrole and g-C3N4 at 40°C and continue stirring and reacting for 10 h. Centrifuge the product, rinse and filter it with anhydrous ethanol and ultrapure water alternately, and place it in a vacuum drying oven at 40°C for 12 h to obtain black In2O3 / PPy / g-C3N4 powder. The obtained powder was placed in a tube furnace and heated to 350°C for a short time (30 min) annealing at a heating rate of 5°C / min in a static air atmosphere to obtain a gray-black In2O3 / PPy / g-C3N4 heterojunction powder material.
[0057] The preferred embodiment 1 of the present invention has the highest sensitivity to CO2 gas under visible light irradiation. Since the pyrrolic nitrogen of PPy has an adsorption effect on CO2, the influence of humidity on CO2 is reduced, which proves that the heterojunction material with a suitable ratio can achieve the best response to CO2 gas.
[0058] Example 2
[0059] The other conditions were the same as those in Example 1, except that in step (7), the amount of pyrrole added was 20 μl.
[0060] Example 3
[0061] The other conditions were the same as those in Example 1, except that in step (7), the amount of pyrrole added was 60 μl.
Claims
1. A method for preparing an In2O3 / PPy / g-C3N4 heterojunction sensing material for CO2 gas detection at room temperature. Characterized in that: Through in-situ polymerization, utilizing the high conductivity and low-temperature sensing of PPy, the adsorption of CO2 by pyrrole N, and the excellent visible light absorption ability, the In2O3 / PPy / g-C3N4 organic-inorganic heterojunction material was designed and synthesized to achieve high-sensitivity detection of CO2 in a low concentration range at room temperature.
2. According to claim 1, wherein In2O3 is a hollow tubular structure obtained by calcining an In-MIL-68 precursor.
3. According to claim 1, wherein g-C3N4 is a nanosheet prepared by thermal decomposition of urea.
4. According to claim 1, wherein PPy is a black powder obtained by adding FeCl3·6H2O aqueous solution dropwise to a pyrrole dispersion.
5. According to claim 1, wherein In2O3 / PPy is obtained by suspension polymerization of In2O3 and pyrrole.
6. According to claim 1, wherein g-C3N4 / PPy is obtained by polymerizing g-C3N4 nanosheets and pyrrole, and then adding FeCl3·6H2O to react.
7. According to claim 1, wherein the In2O3 / PPy / g-C3N4 heterojunction material is obtained by reacting In2O3, pyrrole and g-C3N4 and calcining them in a tubular furnace.
8. According to claim 1, wherein the CO2 detection performance is optimized by adjusting the ratio of pyrrole.
9. Use of an In2O3 / PPy / g-C3N4 heterojunction material prepared by the method according to any of the preceding claims in a room temperature CO2 gas sensing material.
Citation Information
Patent Citations
Hydrogen sulfide gas detection method based on composite membrane material and sensor
CN111781249A
Flexible inorganic semiconductor resistance type room temperature gas sensor and preparation method thereof
CN113325043A
Polypyrrole coated conductive carbon black / indium oxide composite material as well as preparation method and application thereof
CN114335537A
Gas sensors, and methods of making and using them
WO1986001599A1